Pengaruh Latihan Olahraga Selam terhadap Kapasitas Vital Paru dan Kebugaran Jasmani pada Horas Diving Club Univesitas Sumatera Utara - Batubara, Bagas Hasonangan; Hasibuan, Sanusi; Simatupang, Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of diving training on vital lung capacity and the physical fitness of the Horas Diving Club, University of North Sumatra. The research problem is that there has been no checking of the vital lung capacity and physical fitness of divers at the Horas Diving Club, University of North Sumatra. From the data analysis carried out, the results showed that there was a significant influence of diving sports training on the vital capacity of the lungs of Horas Diving Club, North Sumatra University, with the acquisition of the